2016
DOI: 10.1002/ece3.2048
|View full text |Cite
|
Sign up to set email alerts
|

Tooth wear patterns in black rats (Rattus rattus) of Madagascar differ more in relation to human impact than to differences in natural habitats

Abstract: Dietary characteristics and environmental variables are important selective factors directing ecological diversification in rodents. On Madagascar, the introductions and spread of the commensal black rat (Rattus rattus) can be seen as example cases to study dietary niche occupation and dietary adaptation in an insular environment. We investigate how tooth wear as a measure of dietary adaptation of black rats differs between four distinct habitats (village, manioc fields, spiny forest, and rainforest) with diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 45 publications
3
23
0
4
Order By: Relevance
“…In the case of individuals in the Wild (S) population, which also often invade cultivation areas, it is unsurprising that their tooth surface textures were similar to those of reared pigs (i.e., artificially fed on crops). Winkler et al [ 46 ] also reported that the tooth surface textures of modern small mammals were affected by forest cultivation. Some of the Wild (S) population may have consumed agricultural crops before being hunted, which resulted in the surface texture of their teeth being similar to that of the stall-fed population.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of individuals in the Wild (S) population, which also often invade cultivation areas, it is unsurprising that their tooth surface textures were similar to those of reared pigs (i.e., artificially fed on crops). Winkler et al [ 46 ] also reported that the tooth surface textures of modern small mammals were affected by forest cultivation. Some of the Wild (S) population may have consumed agricultural crops before being hunted, which resulted in the surface texture of their teeth being similar to that of the stall-fed population.…”
Section: Discussionmentioning
confidence: 99%
“…Natural geographical variation in diet, particularly where species have large or heterogeneous ranges, is also likely to affect microwear. DMTA studies have considered differences between geographical regions in pigs [35], rodents [19,29,36,37], deer [18,38], primates [39], lemurs [17] and humans (e.g. [40][41][42]).…”
Section: Intraspecific Factorsmentioning
confidence: 99%
“…Nevertheless, there are few studies on the intra-specific variations in chewing mechanics 31 32 and in diet 33 34 in mammals other than human populations. Moreover, the application of DMTA to rodents is still in its infancy (SSFA 34 35 36 , STA 37 ). Finally, DMTA has never been applied to reconstruct chewing movements, most likely because SSFA does not compute texture direction.…”
mentioning
confidence: 99%